Determinants of bank fragility: evidence from Malaysian commercial banks / Nurul Farhana Mazlan - Mazlan, Nurul Farhana (2014)
When banks are considered fragile and what trigger them to be fragile? This research attempts to answer those questions by measuring bank fragility and identify probable factors determining bank fragility of the Malaysian commercial banking sector during the period of 1996-2011. Previous studies have employed different methods to measure the bank fragility. Among the methods used are event study, "government intervention" in term of liquidity support to detect bank fragility and some prefers to use indicator such as Non-Performing Loan (NPL) to identify bank systemic risk. This research constructs the Banking Sector Fragility Index (BSFI) to measure fragility of commercial bank during the period studied. The index is then used to identify the determinants of commercial bank fragility. Results of BSFI show that the commercial banking sectors are in fragile condition from 1996 until 2000 and in a highly fragile stage between 1996 and 1998 since the BSFI are less than -0.50. In addition, findings based on the Logit regression analysis infer that the likelihood of Malaysian commercial banks to be fragile is significantly determined by total loans to total assets and interbank rate. While, Pooled Ordinary Least Squares (OLS) proved that bank specific factors and macro-economic factors have relationship with the level of BSFI.